Modulation of ERG retinal sensitivity parameters with light environment and photoperiod - Beaulieu, Catherine; Rufiange, Marianne; Dumont, Marie; Lachapelle, Pierre (Documenta ophthalmologica, 2009)
It has been reported that the sensitivity to light of the circadian system of animals and human subjects can be modulated following long-term exposure to a given light environment. Animal studies have also shown that long-term exposure to a light regimen, or light history, will have a significant impact on the retinal structure and function, the objective of which being to regulate the number of photons processed daily by the retina, a phenomenon referred to as photostasis. The existence of such a mechanism has never been explored in humans. In the present study, daily light exposure was continuously recorded in two populations of full-time workers: one group working indoors, in a relatively dim environment without access to natural light, and one group working mainly outdoors in natural bright light. The effect of seasonal changes in the length of the photoperiod was also examined. Retinal sensitivity, as determined with scotopic and photopic electroretinograms (ERG), was compared between these two groups. Indoor workers received less light than outdoor workers, the difference being significant only during work hours. A dim work environment was associated with greater retinal sensitivity in scotopic conditions and lower retinal sensitivity in photopic conditions when compared to a bright work environment. The above differences in retinal sensitivity were evidenced only in workers studied during the months with the shortest photoperiod (Fall–Winter). These results support the hypothesis that, similar to what was previously demonstrated with animal models, the human retina adapts its sensitivity to light according to previous chronic light history, suggesting the existence of a photostasis phenomenon in the human retina as well.